The reductive object : A survey of the minimalist aesthetic in the 1960s. - Institute of Contemporary Art, Boston; Prokopoff, Stephen S. (Boston : Institute of Contemporary Art Boston, 1979)
Andre, Carl ; Baer, Jo ; Bell, Larry ; Riverhead (New York) ; Humphrey, Ralph ; Irwin, Robert ; Judd, Donald ; Kauffman, Craig ; LeWitt, Sol ; Mangold, Robert ; Marden, Brice ; Martin, Agnes ; Morris, Robert ; Ryman, Robert ; Smithson, Robert ; Stella, Frank
The reductive object : A survey of the minimalist aesthetic in the 1960s, Institute of Contemporary Art Boston, March 7 - April 29, 1979
Engels
boek